COVID-19 Migration Policy Measures for International Students and Graduate Job Searchers: A Lost Round in the Battle for Brains - de Lange, Tesseltje (Frontiers in Human Dynamics, 2020)
Global policy responses to COVID-19 in terms of international students migration and foreign graduate job searchers demonstrate huge disparities and insecurities regarding their migration status. Three main issues can be distinguished in COVID-19 related visa and migration policy measures for international students and graduate job searchers: Policies on returning or remaining during the lockdown, policies on extending students’ and job searchers legal stay and policies allowing new students to arrive. This contribution maps migration policy responses in five popular destination countries across the globe. This mapping exercise identifies three patterns of response to COVID-19: Facilitating, blocking or ambiguous. The policy responses are critically assessed in the context of the so called “battle for brains”. From a concise overview of the interests at stake with international student migration policy a change in perspective from development of the country of origin to development of the labor markets and innovation in the countries of destination can be distinguished. International students are stuck between the interests of their countries of origin, the destination countries and HEI, and their own interests in receiving an international education, onward migration, and an international career are not always represented. The COVID-19 crisis has shown how in some countries of destination, international students and graduates, although high-skilled and ‘home-trained’, are not treated as belonging to the country of destination. Their home is still in their country of origin. The crisis reveals that they may be little more than future (high-skilled) guest workers, disposed of in times of crisis.